Expression of human telomerase RNA component (hTR) in basal cell carcinoma and squamous cell carcinoma of skin - Gałka, Sabina; Mazurek, Urszula; Brzezińska-Wcisło, Ligia; Pierzchała, Ewa; Wilczok, Tadeusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
hTR subunit of telomerase is known to be responsible for cell immortalization. The aim of the study was to examine transcriptional activity of the hTR gene by QRT-PCR in BCC (basal cell carcinoma) and SCC (squomas cell carcinoma) and to estimate the correlation between hTR expression and malignancy grade of the disease. Molecular analysis was carried out on biopsy specimens collected from patients with BCC (n=9) and SCC (n=9). Levels of hTR mRNA was measured by real-time QRT-PCR technique in total RNA extracted from the studied material. hTR mRNA was present in all 18 cases. Mean copy number of hTR mRNA in 1 µg of total RNA was 1.58x10 4 in BCC samples and 6.01x10 4 in BCC samples. Expression of hTR encoding gene was significantly higher in SCC as compared to BCC (t-test with separate estimation of variance, p=0.001). Quantitative analysis performed in this study indicates that the transcriptional activity of hTR gene is elevated in SCC as compared to BCC (approximately 3.8 times). Thus, we suggest that expression of the hTR subunit of telomerase may be involved in the progression of malignant transformation in the course of the disease.